Da serra à costa: migração e modernização peruana na obra de Mario Vargas Llosa (1950-1960) - Sacoman, Mateus Barroso [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Writer, playwright, essayist and literary critic, Mario Vargas Llosa was awarded with the Nobel Prize for Literature in 2010, has become one of the leading intellectual figures of contemporary Peru. Many of his books were influenced by their perception of Peruvian society and his own experiences, achieving recognition with books like Los Jefes, La ciudad y los perros, La Casa Verde, Los Cachorros and Conversación en la Catedral. These books were produced in a troubled period of Peruvian society, immersed in the modernization and internal migration of the mountain to the coast during the 1950s and 1960s process. And these books will be the subject of our investigation in this study, which aims to analyze the Peruvian writer engaged as a writer that also affects its society through novels, using them as a tool to express himself. Also seeking to understand the extent to which his works of the 1950s and 1960s dialogue with other areas of knowledge in the debates on the problems faced by your society. We also seek to understand your conceptions of literature, romance and the role of the writer, in order to place him in his intellectual trajectory, assuming that the novels studied in this research can be understood as an opportunity which guarantees the expression of his intellectual restlessness, seeking to establish typifications and interpretations around the Peruvian and Latin America reality. This work also aims to identify how the plots of the novel demonstrate these transformations, taking into consideration the engaged literature proposed by Vargas Llosa and how these changes occurred and led to a reconfiguration of the way of understanding the concept of criollo, deeply investigating the social relationships between already residing in Lima inhabitants and migrants coming from the mountain

Escritor, dramaturgo, ensaísta e crítico literário, Mario Vargas Llosa, foi laureado com o prêmio Nobel de Literatura no ano de 2010, tornou-se uma das principais figuras intelectuais do Peru contemporâneo. Muitos de seus livros foram influenciados pela sua percepção sobre a sociedade peruana e suas próprias experiências, alcançando reconhecimento com obras como Los Jefes, La ciudad e los perros, La Casa Verde, Los Cachorros e Conversación en la Catedral. Estas foram produzidas em um período conturbado da sociedade peruana, imersa no processo de modernização e migração interna da serra para a costa durante as décadas de 1950 e 1960. E são estas obras que serão objeto de investigação neste estudo, que visa analisar o escritor peruano como um literato engajado que intervém em sua sociedade também através dos romances, utilizando-os como instrumento para se expressar. Procurando compreender também, até que ponto suas obras das décadas de 1950 e 1960 dialogam com outras áreas do conhecimento nos debates sobre os problemas enfrentados por sua sociedade. Buscando, ainda, entender suas concepções sobre literatura, romance e o papel do literato, com o intuito de situá-lo em sua trajetória intelectual, partindo do pressuposto que os romances estudados nesta pesquisa podem ser compreendidos como uma oportunidade que lhe garante a expressão de sua inquietude intelectual em busca de estabelecer tipificações e interpretações em torno da realidade peruana e latino-americana. Pretende-se também identificar como os enredos do romance demonstram essas transformações, levando em consideração a literatura engajada proposta por Vargas Llosa e como essas mudanças ocorreram e levaram a uma reconfiguração do modo de compreender o conceito de criollo, investigando profundamente as relações sociais entre os habitantes já residentes em Lima e os migrantes advindos da serra
Keywords: Vargas Llosa, Mario 1936; História; Miscigenação - Peru; Imigrantes - Aspectos sociais; Literatura peruana; Vida intelectual; Peru - História - Migração; History